A constitucionalidade da Lei 13.303/2016: a distinção entre sociedades estatais “empresárias” e “não empresárias” - Justen Filho, Marçal (2018)
Article 1 of Law 13303 has aroused controversy in determining that its provisions apply to both state entities that exploit economic activity and those that provide public services. The issue was brought to the attention of the STF itself, invoking a violation of the constitutional distinction between public companies that provide public services and exploiters of economic activity. But the legal discipline has not been appreciated under a specific prism, related to the distinction between business and non-business, as enshrined in the Civil Code.